2017
DOI: 10.3390/batteries3040041
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Cs2CO3 Additive in KOH Electrolyte Used in Ni/MH Batteries

Abstract: Abstract:The effects of Cs 2 CO 3 addition in a KOH-based electrolyte were investigated for applications in nickel/metal hydride batteries. Both MgNi-based and Laves phase-related body-centered cubic solid solution metal hydride alloys were tested as the anode active materials, and sintered β-Ni(OH) 2 was used as the cathode active material. Certain amounts of Cs 2 CO 3 additive in the KOH-based electrolyte improved the electrochemical performances compared with a conventional pure KOH electrolyte. For example… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 53 publications
0
5
0
4
Order By: Relevance
“…Ni-MH pilleri 1960'lı yıllarda keşfedilmiş olup ticari olarak 1989 yılından bu yana elektrikli aletler, robotlar, vakum temizleyiciler, elektrikli oyuncaklar, kablosuz telefonlar, cep telefonları, acil ışıklandırma sistemleri, dizüstü bilgisayarlar, hesap makineleri, taşınabilir kayıt cihazları, oyuncaklar, fotoğraf ve video ekipmanları, kablosuz fare ve klavyeler, hibrit elektrikli araçlar, endüstriyel enerji depolama ve hafif raylı sistemler gibi pek çok alanda kullanıma sahiptir [9][10][11]. Ni-MH pilleri diğer pil teknolojilerine göre geniş sıcaklık çalışma aralığı, uzun kullanım süresi ve yüksek spesifik güç gibi çok sayıda önemli özelliğe sahiptir.…”
Section: Gi̇ri̇ş (Introduction)unclassified
See 2 more Smart Citations
“…Ni-MH pilleri 1960'lı yıllarda keşfedilmiş olup ticari olarak 1989 yılından bu yana elektrikli aletler, robotlar, vakum temizleyiciler, elektrikli oyuncaklar, kablosuz telefonlar, cep telefonları, acil ışıklandırma sistemleri, dizüstü bilgisayarlar, hesap makineleri, taşınabilir kayıt cihazları, oyuncaklar, fotoğraf ve video ekipmanları, kablosuz fare ve klavyeler, hibrit elektrikli araçlar, endüstriyel enerji depolama ve hafif raylı sistemler gibi pek çok alanda kullanıma sahiptir [9][10][11]. Ni-MH pilleri diğer pil teknolojilerine göre geniş sıcaklık çalışma aralığı, uzun kullanım süresi ve yüksek spesifik güç gibi çok sayıda önemli özelliğe sahiptir.…”
Section: Gi̇ri̇ş (Introduction)unclassified
“…Ni-MH pilleri diğer pil teknolojilerine göre geniş sıcaklık çalışma aralığı, uzun kullanım süresi ve yüksek spesifik güç gibi çok sayıda önemli özelliğe sahiptir. Bu özellikler son yıllarda yeniden pek çok araştırmacının ve enerji pazarının yeniden bu piller üzerinde çalışmalar yapmasına neden olmuştur [10]. Ni-MH pilinde pozitif elektrot olarak hidrojen absorplayan metal alaşım (metal hidrit, MH) kullanılırken negatif elektrot olarak deşarj durumunda nikel hidroksite indirgenen nikel oksihidroksit (NiOOH) kullanılmaktadır [12].…”
Section: Gi̇ri̇ş (Introduction)unclassified
See 1 more Smart Citation
“…The capacity the BCC-C14 alloy was 30% higher than the classic AB 5 alloy. In the research and development of the new electrolyte, many samples of the modified aqueous KOH were tested [20]. Research has shown that the way to increase energy density is to achieve higher cell voltage; therefore, the focus was on IL fluids (ionic liquid), consisting of only anions and cations and characterised by, among other features, high thermal stability, high ion conductivity and non-flammability.…”
Section: Recent Developments In the Field Of Nimh Batteriesmentioning
confidence: 99%
“…In 2016, we reported that the reduction of the corrosion nature of the alkaline KOH electrolyte can be accomplished by selection of both adequate combination of alkaline species [22] and salt additives [23]. In this Special Issue, the effects of adding Cs 2 CO 3 salt in the electrolyte was further investigated, and a newly formed surface amorphous oxide was credited for the reduction of surface oxidation of the MgNi-based MH alloy [24]. Another breakthrough was using the ionic liquid to replace the aqueous KOH solution as the electrolyte [8].…”
Section: Electrolytementioning
confidence: 99%